HPV infection and breast cancer risk: insights from a nationwide population study in Taiwan - Lin, Chuck; Tsai, Stella Chin-Shaw; Huang, Jing-Yang; Lin, Frank Cheau-Feng (Frontiers in Oncology, 2023)
Background: The prevalence of cancer, specifically breast cancer, has raised globally. The etiology of breast cancer has been attributed to age, genetic mutations, reproductive history, hormone therapy, lifestyle factors, and viral infections. The human papillomavirus (HPV) has been one of the most widespread sexually transmitted infection in the United States. The role of HPV in breast oncogenesis was hypothesized before, yet the association remained unclear. Methods: In this study, we employed a nationwide population study using centralized patient data managed by the Ministry of Health and Welfare in Taiwan and the Taiwan Cancer Registry database. The breast cancer incidence rates of the 467,454 HPV patients were compared to twice as many non-HPV patients with matching sex and age. Cumulative breast cancer incidence rates were presented by a Kaplan-Meier curve, and the relative risk of breast cancer for HPV and non-HPV patients were calculated using Cox-regression model. Results: Our results indicated a crude hazard ratio (HR) and an adjusted hazard ratio (aHR) of 2.336 and 2.271, respectively, when comparing the risk of breast cancer in the HPV and non-HPV group. The risk of breast cancer was comparable or higher than those of head and neck cancer (aHR=1.595) and cervical cancer (aHR=2.225), which both were found to have causal relationships with HPV. The Kaplan-Meier curve further illustrated a higher cumulative risk across 84 months for HPV patients (p<.0001). Besides HPV, age (p<.0001), insurance providers (p<.001), and comorbidities such as abnormal liver function (aHR=1.191, p=.0069) and hyperlipidemia (aHR=1.218, p=.0002) were found to be correlated with higher risks of breast cancer.A correlation between HPV and breast cancer can be inferred using national health databases. More molecular studies are required to understand the mechanism of the virusinduced oncogenesis of the breast.